Flesh and Nothing More: Configuration of Fleshed Discourse in La carne de René[Rene ́s Flesh] by Virgilio Piñera - Mora Moreno, Sergio Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article analyzes the novel La carne de René [Rene ́s Flesh] by the Cuban writer Virgilio Piñera, from point of view of the construction of the hegemonic discourse – that I call “fleshed”- which builds and defines the bodies of its characters and their subjectivities. This paper, then, inquires into the discursive mechanisms (such as parody and the struggles between power-knowledge about the body) that constitute the flesh discourse and how it operates in the individuals of this literary universe (especially in René, the protagonist), so that they can be understood as subjects made up of mere flesh subjected to pain, and therefore unable to build a spiritual life. Despite exercising resistance to the flesh discourse, René succumbs to it, failing to propose an individuality beyond this discourse. Because of this, he has no choice but to accept that he is a being made of flesh and nothing more.